Effectiveness of cognitive rehearsal programs for the prevention of workplace bullying among hospital nurses: a systematic review and meta-analysis - Yulliana Jeong; Hye Sun Jung; Eun Mi Baek (BMC, 2024)
Abstract Background To solve the problem of workplace bullying among nurses, it is necessary to review the effects of interventions and generalize the findings. We conducted a systematic literature review and meta-analysis to evaluate the effects of cognitive rehearsal programs on workplace bullying among hospital nurses. Methods Data were collected from March 30 to April 11, 2021, and 11,048 journal articles published in South Korea and internationally were examined across eight databases. Nine articles were selected for inclusion in the systematic literature review; five of the nine studies were included in the meta-analysis. For randomized controlled trials, the risk of bias was evaluated, and for non-randomized controlled trials, the study quality was evaluated using the Risk of Bias for Non-randomized Studies version 2.0. Egger's regression test was performed to determine publication bias. Results Of the nine articles selected for this study, two were randomized controlled trials and seven were non-randomized controlled trials. The I2 value was 18.9%, indicating non-significant heterogeneity. The overall effect size of the cognitive rehearsal programs was -0.40 (95% confidence interval: -0.604 to -0.196; Z = -3.85; p = .0001) in a random-effects model, indicating a large effect size with statistical significance. Conclusions Therefore, cognitive rehearsal programs that address workplace bullying among hospital nurses are effective. Health policymakers must implement cognitive rehearsal programs in a policy manner to address the problems of bullying in the workplace.